Model Sistem Pendukung Keputusan Penentuan Strategi Peningkatan Kinerja Guru Menggunakan Metode Analytic Network Process - Zaqi Kurniawan; Marimin Marimin; Rusdah Rusdah (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
All parties are aware that teacher performance is directly proportional to improving the quality of education. Not a few teachers work under predetermined work standards, conditions like this are caused by low work enthusiasm which results in decreased performance. If we observer the passion of work in the form of sine graph which one day will meet a saturation point if there are no preventive and curative efforts eithers form himself or guidance form his superior. One of the efforts taken is to impose teacher performance assessment to ensure a quality learning process at levels of education. Teacher performance appraisal needs to be carried out so that the functions and duties in the functional teacher positions and duties in the functional teacher positions are carried out by the applicable rules and code of ethics. On that basis, a decision support system was created using the Analytical Network Process method which can determine teacher performance improvement strategies, based on objective performance appraisals and make decisions that become more efficient.